The The Concept of Sustainable Finance in Islam: A Study - Ainul Mardiah; Muhammad Ilmi; Erwan Setyanor (PT. Pustaka Andil Lestari, 2025)
This study aims to explain the concept of sustainable finance from an Islamic perspective. The study analyzed various academic journals and related literature, using a qualitative approach through a literature review. The study found that Islamic sustainable finance focuses not only on financial returns but also on environmental needs, social justice, and compliance with Sharia principles. Values such as justice (al-'adl), balance (al-mizan), and profit (al-maslahah) are its core foundations. The study shows that these principles are consistent with the Sustainable Development Goals (SDGs) and can be implemented through Islamic financial products such as green sukuk and productive waqf. This research contributes to a deeper understanding of the integration of Islamic finance with global sustainability issues.